Characteristics and mechanism of strong dynamic load mine pressure in large mining height full-mechanized caving face with multiple thick and hard roof - Zhen ZHANG; Zhizeng HUANG; GANG XU; Xiaogang LIU; Qianjin LIU; Tielin ZHAO; Xingyu LIN (Meitan xuebao)
In view of the problems of strong mine pressure such as rapid shrinkage of hydraulic support column and easy support crushing in working face under the fully mechanized caving face with large mining height in multi-layer thick and hard roof of extra-thick coal seam in Yushen mining area, the support working resistance and roof subsidence during the mining period of the working face are systematically monitored by using column pressure sensor and displacement sensor, and the macroscopic characteristics of mine pressure behavior and the linkage between near and far field overburden movement and mine pressure are analyzed. The characteristics of mine pressure in fully mechanized caving face with large mining height and multi-layer thick and hard roof were clarified, the spatial form of multi-layer thick and hard roof breaking and the evolution law of overburden structure were obtained, and the mechanism of mine pressure was expounded. The mechanical model of overburden structure in different layers of low, medium and high layers was established considering the bending deformation in front of the coal wall and the stress correlation between the layers of multi-layer thick and hard roof. The criterion of rock failure instability and the critical support strength of the support in different layers were given. The results show that the mining of fully mechanized top coal caving face with multi-layer thick and hard roof and large mining height not only has the characteristics of “obvious regional pressure, rapid increase of pressure resistance, large and small periodic pressure, periodic strong dynamic load pressure”, but also presents the new characteristics of multiple continuous or short-distance intermittent large periodic pressure during strong dynamic load pressure. During the period of strong dynamic load, the degree of continuous large-period rock pressure shows a trend of increasing first and then decreasing,the periodic strong dynamic load pressure of the working face is irregular, with 4 to 10 small cycles,an interval of 120.9−241.9 m and an average interval of 161 m. During the period of strong dynamic load pressure, the mine pressure appears abnormally strong. The high-level rock stratum is located more than 70 m above the coal seam. After the thick and hard rock stratum in the middle is broken, the effective contact and support force of the high-level “hinged beam” is reduced, resulting in the failure and instability of the high-level hinged beam, which in turn leads to the strong dynamic load pressure phenomenon of multiple continuous or short-distance intermittent large-cycle pressure in the working face. The reasonable support strength of the support is 1.897 MPa when the middle “non-articulated beam” structure is broken and unstable. The reasonable support strength of the support corresponding to the rotary deformation instability of the “hinged beam” is 2.470 MPa, and the reasonable support strength of the support corresponding to the sliding instability is 3.180 MPa. The existing high-strength support is difficult to effectively control the strong mine pressure of the roof. It is necessary to adopt the means of roof weakening to control the surrounding rock of the stope. The research results have important guiding significance for the surrounding rock control of multi-layer thick and hard roof mining in extra thick coal seam.